FAMILY SUPPORT IN REDUCING EMOTIONAL STRESS FOR THE ELDERLY IN THE SOCIETY 5.0 ERA IN PEKIK NYARING VILLAGE - Regina Dwi Wulandari; Tamrin Bangsu; Ishak Fadlurrohim (Universitas Negeri Medan, 2025)
In the rapidly evolving digital landscape of Society 5.0, characterized by advanced technology integration into daily life, elderly individuals often face heightened emotional stress due to isolation and adaptation challenges. This phenomenon is particularly pronounced in rural areas like Pekik Nyaring Village, where traditional family structures intersect with modern technological demands. Recognizing the pivotal role of family support in mitigating such stress, this study explores how familial interventions can foster emotional resilience among the elderly. This study aims to analyze the support of the family in reducing emotional stress in the elderly in Pekik Nyaring Village, Central Bengkulu Regency. The approach used was qualitative with in-depth interviews with 12 informants, consisting of 6 elderly aged 60–78 years and 6 family members who care for the elderly. This study examines four dimensions of family support, namely emotional, instrumental, informational, and appraisal. The results showed that families provide emotional support through regular communication and attention, instrumental support in the form of assistance with daily activities and finances, informational support in the form of advice and direction, and esteem support through motivation and recognition. These four dimensions have been shown to reduce levels of emotional stress triggered by loneliness, health problems, economic problems, and the loss of a partner. In the context of Society 5.0, families also play a role as technological mediators by introducing telephones, video calls, or simple social media to the elderly. Despite obstacles such as limited digital literacy, distance, and family busyness, adaptive strategies such as gradual teaching and empathetic communication help maintain the emotional stability of the elderly. Thus, the quality of family support is key to improving the well-being of the elderly in the digital era. Keyword: Family support; Emotional stress; Elderly; Era Society 5.0